Design and characterisation of food grade powders and inks for microstructure control using 3D printing. (March 2018) - Holland, Sonia; Foster, Tim; MacNaughtan, William; Tuck, Chris
Abstract: Additive Manufacturing techniques have been previously applied to food materials with direct consumption in mind, as opposed to creating structural ingredients as shown in this study. First, semi-crystalline cellulose was mechanically treated by ball milling to render an amorphous powder, which has been characterised. Requirements for the subsequent recrystallization of this powder with a view to structuring have been determined through the control of moisture and thermal energy. Food inks based on xanthan gum have been formulated to enable successful jetting with a FujiFilm Dimatix ink jet printer. The polymer inks were subsequently jetted onto the amorphous cellulose powder to observe powder-binder interactions. Material combinations and parameters were optimised to produce cohesive geometric structures. The results of this study are promising when looking towards using these materials in a binder jetting additive manufacturing technique using designer particles and inks to create structures for use in food products. Highlights: Amorphous cellulose created via ball milling and selectively recrystallized. Xanthan Gum incorporated into a printable ink media. Cellulose powder and ink combined in an ink jetting process. 2D jetting onto powder shows promise to create 3D food microstructures.